2019
DOI: 10.1108/ajems-12-2018-0404
|View full text |Cite
|
Sign up to set email alerts
|

Does the chief audit executive gender matter to internal audit effectiveness? Evidence from Tunisia

Abstract: Purpose The purpose of this paper is to investigate whether chief audit executive (CAE) gender has a significant impact on the internal audit function (IAF) effectiveness as proxied by the extent to which the internal audit function uses quality assurance techniques. Design/methodology/approach This study uses a multivariate regression model to analyze the association between CAE gender and the use of quality assurance techniques in fieldwork as a proxy for IAF effectiveness. Data were collected using a surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 80 publications
1
5
0
2
Order By: Relevance
“…Faktor lainnya yang turut membantu entitas dalam mencapai fungsi internal audit yang dimiliki adalah terkait gender kepala departemen internal audit (chief audit executive-CAE). CAE perempuan cenderung akan menjadikan fungsi internal audit lebih efektif (Oussii dan Klibi, 2019;Hardies, Breesch, dan Branson, 2015;Ittonen, Vähämaa, dan Vähämaa, 2013). Pemimpin perempuan cenderung lebih berkompetensi, stabil secara emosional dan independent dari pada laki-laki (Dennis dan Kunkel, 2004).Stewart, dan Munro (2007) menunjukkan adanya direktur perempuan memiliki komunikasi yang lebihbaik.…”
Section: Internal Auditunclassified
“…Faktor lainnya yang turut membantu entitas dalam mencapai fungsi internal audit yang dimiliki adalah terkait gender kepala departemen internal audit (chief audit executive-CAE). CAE perempuan cenderung akan menjadikan fungsi internal audit lebih efektif (Oussii dan Klibi, 2019;Hardies, Breesch, dan Branson, 2015;Ittonen, Vähämaa, dan Vähämaa, 2013). Pemimpin perempuan cenderung lebih berkompetensi, stabil secara emosional dan independent dari pada laki-laki (Dennis dan Kunkel, 2004).Stewart, dan Munro (2007) menunjukkan adanya direktur perempuan memiliki komunikasi yang lebihbaik.…”
Section: Internal Auditunclassified
“…The IIA (1999) defines the IA as an independent and objective advisory investigation to protect institutions’ funds and add value. According to the results of studies conducted on institutions in Arab countries, IA’s independence and objectivity are among the main factors that are positively affected by the presence of independent risk management committees, ACs size, and firms connected to the finance sector (Alhajri, 2017; Al-Twaijry et al, 2004), sound CG (Alaraji, 2020), the gender of chief audit executive (Muqattash, 2017; Oussii & Klibi, 2019), and salary (Muqattash, 2017). As presented in Table 6, the investigation revealed that very limited studies has been directed to the IAFs and the quality of small-medium enterprises (Shaiti & Al-Matari, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…The effectiveness internal audit function can be measured by several dimensions, such as competence, independence, compliance with professional standards (Kaawaase et al, 2021), and the sufficiency of audit committee members (Oussii & Klibi, 2019). A sufficient audit committee members can enhance control activities and participate reducing the firm's risk.…”
Section: Discussionmentioning
confidence: 99%
“…To measure internal audit quality, we used the number of the audit committee in the companies. Oussii & Klibi (2019) stated that the number of internal audit committees was significantly associated with higher quality financial reports. Internal audit committee provides assessment on preparing financial reports by using quality assurance techniques in the business activities.…”
Section: Variable Descriptionsmentioning
confidence: 99%